2015
DOI: 10.1590/1808-1657000492013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da ação de uma virose na produção e qualidade de tubérculos de batata-doce

Abstract: ABSTRACT:The Western region of São Paulo State, Brazil, is responsible for approximately 40% of the production of sweet potato (Ipomoea batatas L.) in the state, even under lowtechnology. The study aimed to evaluate the impact of viruses on sweet potato production variables. The experiment was conducted in Presidente Prudente, São Paulo, Brazil, in a commercial sweet potato crop of pink group, cv. Canadense, with and without virus. In three randomly chosen plots of 10 x 4 m in each half of the field (with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the mini cutting system, the seedlings have better sanity (Montes, 2012) which results in greater yields in the field (Rós et al, 2012;Montes et al, 2015). However, as the nutritional status of seedlings plays an important role in the phases of induction and root formation (Cunha et al, 2009), crop nutritional management in this phase is very important.…”
Section: Introductionmentioning
confidence: 99%
“…In the mini cutting system, the seedlings have better sanity (Montes, 2012) which results in greater yields in the field (Rós et al, 2012;Montes et al, 2015). However, as the nutritional status of seedlings plays an important role in the phases of induction and root formation (Cunha et al, 2009), crop nutritional management in this phase is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the maximum productive potential of the cultivar Crioula, a cultivar with medium productivity, was not reached, and it may be associated with the low health of the seedlings and its great genetic variability. According to Montes, Paulo and Montes R. (2015) it is important to check the health of sweet potato seedlings, because when infected with viruses they present low production and lower commercial value. Martins et al (2014), showed that sweet potato presents high genetic diversity among its clones, varying from the place of origin of the material and due to the occurrence of natural crossings of the materials, intensifying the disease problems.…”
Section: Resultsmentioning
confidence: 99%
“…Equal lowercase letters in the lines, between the fertilization conditions, for each cultivar, do not differ from each other by the T test 5%.However, among the virus-free sweet potato cultivars, there was no statistical difference for the number of roots; Rubissol and Cuia had a greater number of cracks; Longest rubissol and gourd with the largest diameter. Cultivar Crioula produced the smallest number, size, length of roots and cracked roots, regardless of the cultivation condition Montes, Paulo Montes R. (2015). report that cultivars without clonal cleaning of viruses have low productivity, related to the smaller number and weight of roots, limiting production and, consequently, the commercial value due to a greater amount of small and deformed roots.…”
mentioning
confidence: 93%
“…Two sweet potato cultivars, BRS Amélia and BRS Rubissol, were evaluated from the Embrapa Clima Temperado Agricultural Research Corporation. The genotypes were grown from January to June 2018 in an experimental area at the Federal University of Viçosa, Viçosa, Minas Gerais State, Brazil (20°45′49″ S and 42°49′28″ W, 650 m above sea level), following the recommended crop management practices (Montes, 2013). The roots were harvested and manually selected 160 days after transplanting.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%